Vaccination coverage and factors associated with incomplete childhood vaccination among children aged 12-59 months in the Municipality of Miagao, Iloilo, Philippines. - Celis, Ma. Jascha Lane D.; Delicana, Katie B.; Deopido, Anarey M.; Kang Bacale, Keanah Marie F.; Labasan, Van Karlo L.; Ladiao, Riza Mae.; Militante, Kriza Marie; Paguntalan, Jaypee M.; Sabusap, Von Erjun P. (2019.)
Vaccination aims to reduce the morbidity and mortality among young children against various infectious diseases. The intervention becomes more effective if young children receive the full course of the recommended vaccination doses. However, not all young children are fully immunized due to several factors. Therefore, this study is conducted to describe the coverage and determine the factors associated with incomplete vaccination among children aged 12-59 months in the Municipality of Miagao, Iloilo Province. A cross-sectional study was conducted in Miagao, Iloilo from April 15 to 29, 2019. The study included children born form May 11, 2014, to April 11, 2018, whose mothers are residents of Miagao, Iloilo. A total of 515 children aged 12-59 months were randomly selected using two-stage random sampling design. Data of mothers and children were collected from the Target Client Lists in the Municipal Health Office (MHO). All data were encoded and analyzed using SPSS v21. Binary logistic regression was performed to determine the factors associated with incomplete vaccination. The prevalence of incomplete vaccinated children was 71.26%. Significant factors associated with incomplete vaccination were children delivered at home (AOR = 2.1; 95% CI: 1.32-3.36) and children born from mothers who had two or less postnatal visits (AOR = 3.4; 95% CI: 1.39-8.44). The age of the mothers and the number of antenatal visits of mothers during pregnancy did not influence the outcome. Maternal related factors such as the place of child delivery and the number of postnatal visits of mothers were independent factors for incomplete vaccination. Therefore, the study recommends education of mothers on the importance of postnatal visits, and the enhancement of maternal health services, especially the promotion of facility-based delivery.
Research Paper (Undergraduate, Bachelor of Science in Public Health0 College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Children Vaccination -- Maiagao, Iloilo